2010
DOI: 10.1182/blood-2009-01-199927
|View full text |Cite
|
Sign up to set email alerts
|

Soluble lymphotoxin is an important effector molecule in GVHD and GVL

Abstract: Tumor necrosis factor (TNF) is a key cytokine in the effector phase of graftversus-host disease (GVHD) after bone marrow transplantation, and TNF inhibitors have shown efficacy in clinical and experimental GVHD. TNF signals through the TNF receptors (TNFR), which also bind soluble lymphotoxin (LT␣3), a TNF family member with a previously unexamined role in GVHD pathogenesis. We have used preclinical models to investigate the role of LT in GVHD. We confirm that grafts deficient in LT␣ have an attenuated capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…1 d prior to PbAluc infection. TNF and LTa blockade was performed by administering TNFR2-Ig (Enbrel; Amgen, Thousand Oaks, CA), a fusion protein that has been shown previously to inhibit the functional activity of both murine TNF and soluble LTa homotrimers (53). A total of 0.2 mg TNFR2-Ig was administered i.p.…”
Section: Proliferation Assaysmentioning
confidence: 99%
“…1 d prior to PbAluc infection. TNF and LTa blockade was performed by administering TNFR2-Ig (Enbrel; Amgen, Thousand Oaks, CA), a fusion protein that has been shown previously to inhibit the functional activity of both murine TNF and soluble LTa homotrimers (53). A total of 0.2 mg TNFR2-Ig was administered i.p.…”
Section: Proliferation Assaysmentioning
confidence: 99%
“…11 All recipient mice were transplanted and irradiated on day 0, with irradiation doses as follows: BALB/c, 900 cGy; B6D2F1, 1100 cGy; and B6 and bm1.Act-mOVA, 1000 cGy. BALB/c mice were transplanted with 10 7 T cell-depleted (TCD) BM cells from B6 (allogeneic) or BALB/c (syngeneic) donors, with or without the addition of 0.2 ϫ 10 6 CD3 ϩ T cells, or CD4 or CD8 MACS-purified T cells.…”
Section: Bmtmentioning
confidence: 99%
“…This includes an important role of LT signaling in the acceptance of donor stem cells, controlling cuprizone-induced demyelination, the progression of experimental autoimmune encephalomyelitis and the control of lipid metabolism or liver regeneration Lo et al, 2007;Plant et al, 2007;Markey et al, 2009;Ruddell et al, 2009;Tumanov et al, 2009). Studies with different mouse models revealed a role of LTbR signaling in atherosclerosis development (Schreyer et al, 2002;Grabner et al, 2009) and an involvement of LTbR signaling was discovered in the pathogenesis of RA (Fava et al, 2003).…”
Section: Depletion Of Lt Hi Expressing Cells and Curing Autoimmune DImentioning
confidence: 99%